Establishment of reverse transcription recombinase-aided amplification with lateral flow dipstick for the rapid visual detection of Getah virus - Wei, Bingyan; Xing, Lulu; Sun, Siqi; Zhang, Pu; Dong, Yanjun; Yang, Hanchun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionGetah virus (GETV) is a globally spreading zoonotic mosquito-borne virus that primarily affects horses and pigs, causing significant economic losses in the livestock industry. Therefore, there is an urgent need for improved diagnostic methods to manage future outbreaks.MethodsIn this study, we developed a nucleic acid detection assay, reverse transcription recombinase-aided amplification with lateral flow dipstick (RT-RAA-LFD), for the rapid and convenient detection of GETV.ResultsThe RT-RAA-LFD assay could be completed at 40°C for 15 min. Under optimal reaction conditions, the assay demonstrated excellent specificity, with no cross-reactivity observed with other clinically relevant swine pathogens. It achieved a broad detection range and a limit of detection (LOD) of 5.53 × 102 copies/μL, which was lower than that of RT-PCR (5.53 × 103 copies/μL) assay and slightly higher than that of qRT-PCR (5.53 × 101 copies/μL) assay for GETV. When testing 21 blood samples, the results of RT-RAA-LFD were fully consistent with those of the RT-PCR and qRT-PCR assays. In testing 45 tissue samples, the Kappa value for consistency between RT-RAA-LFD and RT-PCR was 0.776 (P < 0.001), with a concordance rate of 95.6% (43/45). The Kappa value for consistency between RT-RAA-LFD and qRT-PCR was 0.845 (P < 0.001), with a concordance rate of 97.8% (44/45).ConclusionsIn conclusion, the RT-RAA-LFD assay shows great potential as a efficient and user-friendly diagnostic tool for GETV screening, particularly in laboratories with limited resources and equipment.